2011
DOI: 10.2110/palo.2010.p10-151r
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Understanding of the Alaska Coastal Current: The Application of a Bivalve Growth-Temperature Model to Reconstruct Freshwater-Influenced Paleoenvironments

Abstract: Shells of intertidal bivalve mollusks contain sub-seasonally to interannually resolved records of temperature and salinity variations in coastal settings. Such data are essential to understand changing land-sea interactions through time, specifically atmospheric (precipitation rate, glacial meltwater, river discharge) and oceanographic circulation patterns; however, independent temperature and salinity proxies are currently not available. We established a model for reconstructing daily water temperatures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…The results of the studies by Gillikin et al . (2005) and Hallmann et al . (2009, 2011, 2012), as well as the present study, provide a strong foundation to examine the variability observed in region‐specific growth rates, the influence of seasonal freshwater influxes and seasonality in the Namu region.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The results of the studies by Gillikin et al . (2005) and Hallmann et al . (2009, 2011, 2012), as well as the present study, provide a strong foundation to examine the variability observed in region‐specific growth rates, the influence of seasonal freshwater influxes and seasonality in the Namu region.…”
Section: Discussionmentioning
confidence: 97%
“…Even though the coast of BC is subject to seasonal freshwater influxes, previous studies have argued that growth rates of this species are controlled more by temperature than by freshwater (Hallmann et al . 2009, 2011), and the changes in δ 18 O shell are strongly controlled by seasonal influxes of freshwater.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations